1999
DOI: 10.1159/000052761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Donepezil in the Treatment of Alzheimer’s Disease

Abstract: Although the underlying pathogenesis of Alzheimer’s disease (AD) is not fully understood, one of its key features is the widespread loss of central cholinergic innervation, known to be fundamental for cognitive processes. This finding led to the hypothesis that pharmacological enhancement of acetylcholine (ACh) neurotransmission may alleviate the symptoms of AD. Currently, cholinergic therapy, particularly cholinesterase (ChE) inhibition, represents the most realistic approach to the symptomatic treatment of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 56 publications
(51 reference statements)
0
31
0
2
Order By: Relevance
“…Thus, mangiferin improved long-term memory in scopolamine-induced amnestic mouse models by inhibiting AChE, like AChE inhibitors previously reported. 3,11) Mangiferin may reverse deficits in hippocampal long-term memory via cholinergic enhancement.…”
Section: Mangiferin Increases Acetylcholine Level Reduced By Scopolammentioning
confidence: 99%
“…Thus, mangiferin improved long-term memory in scopolamine-induced amnestic mouse models by inhibiting AChE, like AChE inhibitors previously reported. 3,11) Mangiferin may reverse deficits in hippocampal long-term memory via cholinergic enhancement.…”
Section: Mangiferin Increases Acetylcholine Level Reduced By Scopolammentioning
confidence: 99%
“…Clinical trials revealed that donepezil (Aricept, previously E2020, Pfizer), a selective noncompetitive inhibitor of acetylcholinesterase (AChE; see Sugimoto et al (2002) for a review), had cognitive benefits in Alzheimer's disease patients afflicted with mild to moderate degrees of dementia (Mintzer and Kershaw, 2003). Presently donepezil is used to treat cognitive deficits associated with Alzheimer's disease (Rogers and Friedhoff, 1998;Doody, 1999;Grutzendler and Morris, 2001). Additionally, this drug has been found to reverse memory deficits in variety of rodent models of learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinesterase inhibitors were the first generation of such candidate therapeutics (11)(12)(13)(14)(15). A second generation of candidate therapeutics has included a series of attempts to inhibit the formation of amyloid plaques.…”
mentioning
confidence: 99%